2018
DOI: 10.1007/s00330-018-5425-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of contrast-enhanced FDG PET/CT in patients awaiting liver transplantation with rising alpha-fetoprotein after bridge therapy of hepatocellular carcinoma

Abstract: • F-FDG PET/CT is a valuable tool for the detection of HCC recurrence • F-FDG PET/CT should be incorporated during routine workup awaiting liver transplantation • Significant correlation was found between AFP level and SUVmax ratio • The best threshold for F-FDG PET positivity was>1.21 • The ideal cut-off value for AFP was >202.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Although RFA is one of the most effective curative treatment modalities for HCC along with surgical resection and liver transplantation, our study and previous studies showed that there is a substantial possibility of EHM even if intrahepatic lesions are stable[ 8 , 16 , 17 ]. Most other studies showed that the most common initial site of recurrence is intrahepatic and that most cases of EHM occur after multiple intrahepatic recurrences with several treatments[ 8 ].…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although RFA is one of the most effective curative treatment modalities for HCC along with surgical resection and liver transplantation, our study and previous studies showed that there is a substantial possibility of EHM even if intrahepatic lesions are stable[ 8 , 16 , 17 ]. Most other studies showed that the most common initial site of recurrence is intrahepatic and that most cases of EHM occur after multiple intrahepatic recurrences with several treatments[ 8 ].…”
Section: Discussionmentioning
confidence: 67%
“…In particular, when tumor marker levels increase without definite aggravation of previous HCC lesions, additional examination for EHM development should be considered. Refaat et al[ 17 ] reported that among 65 patients who underwent loco-regional therapy for HCC and had elevated serum AFP levels, 10 (15.4%) had EHM without intrahepatic tumor recurrence. In addition, Chen et al[ 16 ] reported that among 26 patients who had elevated serum AFP levels without findings of recurrence on conventional imaging studies, 8 (30.8%) experienced EHM.…”
Section: Discussionmentioning
confidence: 99%
“…have recently reported on distinctively higher sensitivity (92.8% versus 74.7%), specificity (94.1% versus 70.6%), and accuracy (93% versus 74%) of FDG PET/CT compared with contrast-enhanced CT for detecting post-interventional HCC recurrence. 107 SUVmax ratio >1.21 was identified as the best threshold (AUC = 0.935; 95% CI 0.868–0.975; p < 0.0001) for indicating intrahepatic or extrahepatic tumor manifestation. 107…”
Section: F-fdg Pet For Metabolic Assessment Of Tumor Viability Follmentioning
confidence: 96%
“…107 SUVmax ratio >1.21 was identified as the best threshold (AUC = 0.935; 95% CI 0.868–0.975; p < 0.0001) for indicating intrahepatic or extrahepatic tumor manifestation. 107…”
Section: F-fdg Pet For Metabolic Assessment Of Tumor Viability Follmentioning
confidence: 96%
See 1 more Smart Citation